An Analysis of Concentration Region on Powerpoint Slides using Eye Tracking - Fergyanto E. Gunawana; Oky Wijaya; Benfano Soewito; Sevenpri Candra; Diana Diana; Cosmas E. Suharyanto (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Powerpoint slides have become one of the essential teaching  tools in academic  for both  offline and  online modes. It may  play  a  useful  role to facilitate  discussion  and  information exchange.  However,  in  our  teaching  experience,  we find  many students utilizing Powerpoint slides beyond their traditional functions.  Many  students   fully  rely on  the  slides  as  the  main learning   materials   and,  in  some  cases,  substituting  textbooks. This  study  intends  to  understand how  students   interact   with the   learning   materials   presented  on  Powerpoint   slides.  The interaction is measured using  an  eye tracker device called  the Eye  Tribe  Tracker. Thirty  sophomore  and  junior  students  are asked  to participate. They are  instructed to learn  a topic in the subject  of Introduction to Algorithm  and  Programming, a basic course  in the  computer science field. During  the  process,  their fixation points  are  monitored  and  are  related to the contents  on the slides. The results are rather surprising. Many students  read the  slides  in  unexpected  manners that  may  compromise   their understanding and  may lead to inaccurate interpretations.